1998
DOI: 10.1080/10408699891274192
|View full text |Cite
|
Sign up to set email alerts
|

Textural Modification of Processing Tomatoes

Abstract: Knowledge of the textural properties of processing tomatoes is crucial to ensuing product acceptability; measurement, control, and optimization of these properties through judicious selection of varieties and control of unit operations results in products that the consumer prefers. It is important to first define the terms texture, rheology, consistency, and viscosity prior to discussing principles of their measurement. The textural properties of processing tomatoes may be measured using both sensory and objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0
8

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(106 citation statements)
references
References 110 publications
4
94
0
8
Order By: Relevance
“…Khachick et al (1992) using HPLC, reported the presence of low levels of chloroplast xanthophylls such as neoxanthin, violaxanthin, lutein-epoxide and lutein, but only when highly concentrated extracts of tomato were obtained from a large batch of raw tomato (2 Kg). Tomato exocarp is sometimes removed by some consumers, and also in some processing operations (Barret et al 1998). However, from the results obtained in our work, it is recommended that exocarp should not be discarded, and should be consumed along with mesocarp, or it can be utilized as source of nutrients due to their high content of nutritional components such as some carotenoids, as lycopene with their antioxidant properties (Stahl and Sies 1996), and their potential reduction of the risk of some diseases (Clinton et al 1996;Gerster 1997).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Khachick et al (1992) using HPLC, reported the presence of low levels of chloroplast xanthophylls such as neoxanthin, violaxanthin, lutein-epoxide and lutein, but only when highly concentrated extracts of tomato were obtained from a large batch of raw tomato (2 Kg). Tomato exocarp is sometimes removed by some consumers, and also in some processing operations (Barret et al 1998). However, from the results obtained in our work, it is recommended that exocarp should not be discarded, and should be consumed along with mesocarp, or it can be utilized as source of nutrients due to their high content of nutritional components such as some carotenoids, as lycopene with their antioxidant properties (Stahl and Sies 1996), and their potential reduction of the risk of some diseases (Clinton et al 1996;Gerster 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Some research reports suggest that lycopene (Bramley 2000;Arab and Steck 2000) and β-carotene (Burri 1997;Erdman et al 1996) may protect against some forms of cancer and heart disease. Removal and discarding of exocarp and seeds from some fresh fruits and vegetables, is a common practice during processing of some fruits such as tomato (Barret et al 1998), ignoring that exocarp can be a good source for some nutrients, in some cases even better than the mesocarp as reported for kumquat by Huyskens et al (1985), and for muskmelon by Flügel and Gross (1982). Some studies have aimed to know the chemical composition of tomato seed oil from tomato processing waste seeking to use it as food ingredient (Sogi et al 1999;Bhullar and Sogi 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The consistency of the homogenate was determined by measuring the distance that the homogenate fl owed in 30 s under its own weight along a level surface (Barret et al, 1998) with a standard Bostwick consistometer (CSC Scientifi c, 1-800-458-2558, USA). Smaller Bostwick values indicate a thicker, higher-consistency tomato product; therefore, smaller values are preferable in tomato processing (García and Barret, 2006).…”
Section: Tomato Quality Determinationsmentioning
confidence: 99%
“…Grape and potato cells can be as large as 150-200 µm (Gray et al, 1999, Konstankiewicz et al, 2002. In tomato fruit, cells can even be larger than 500 µm long (Barret et al, 1998). In the present work, 13 images were necessary to visualise one vascular bundle of beet root.…”
Section: Discussion -Conclusionmentioning
confidence: 99%